2020
DOI: 10.3390/cancers12051115
|View full text |Cite
|
Sign up to set email alerts
|

Central Pathology Review in SENTIX, a Prospective Observational International Study on Sentinel Lymph Node Biopsy in Patients with Early-Stage Cervical Cancer (ENGOT-CX2)

Abstract: The quality of pathological assessment is crucial for the safety of patients with cervical cancer if pelvic lymph node dissection is to be replaced by sentinel lymph node (SLN) biopsy. Central pathology review of SLN pathological ultrastaging was conducted in the prospective SENTIX/European Network of Gynaecological Oncological Trial (ENGOT)-CX2 study. All specimens from at least two patients per site were submitted for the central review. For cases with major or critical deviations, the sites were requested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Even in the scenario of a prospective trial like the SENTIX trial, the central pathology evaluation showed substantial heterogeneity in clinical practice when following protocol requirements [48]. From a group of 300 patients, samples from 83 cases from 37 sites were reviewed in the first round of revisions.…”
Section: Key Pointsmentioning
confidence: 99%
“…Even in the scenario of a prospective trial like the SENTIX trial, the central pathology evaluation showed substantial heterogeneity in clinical practice when following protocol requirements [48]. From a group of 300 patients, samples from 83 cases from 37 sites were reviewed in the first round of revisions.…”
Section: Key Pointsmentioning
confidence: 99%
“…In spite of it, the sensitivity rates of frozen section described in literature are heterogeneous due to the poor precision of frozen section in detecting low-volume metastases (micrometastases -MM -and isolated tumour cells, ITC), which limits its accuracy [31]. Moreover, there are other factors such as pathological processing protocol, team expertise, volume of the centre and nodal metastasis size that may influence the sensitivity of the technique [32][33][34]. Due to this reason, the intraoperative evaluation of SLNs remains a subject of debate, without consensus between international guidelines [1,12…”
Section: Benefits Of Selective Sentinel Lymph Node Biopsy In Cervical...mentioning
confidence: 99%
“…Sentinel node dissection has been used in early-stage cervical cancer. The most common locations of sentinel nodes are below common iliac bifurcation 11 12 . Hence, it is not useful for the detection of PALN metastases.…”
Section: Assessment Of Para-aortic Lymph Node (Paln)mentioning
confidence: 99%